Some problems of the establishment of the legal regime of lands within the territories with special conditions for economic activity - Shakhray, Irina S.; Nahornaya, Anastasiya D. (Journal of the Belarusian State University. Law, 2026)
The article examines the legal regime of lands within territories with special conditions for economic activity. The general features of the legal regime of such lands, arising from preferential regulation of economic activity, are highlighted, as well as specific features determined by the purposes of establishment, the nature of activities, and the specific economic and investment objectives of each of the territories under consideration. It is concluded that the key problem is the lack of systematic consolidation at the level of the Land Code of the Republic of Belarus of the general and specific features of the legal regime of lands within such territories. Proposals for improving land legislation are formulated.